2022
DOI: 10.3390/buildings12071014
|View full text |Cite
|
Sign up to set email alerts
|

Research on Thermal Response Behavior of the Intumescent Coating at High Temperature: An Experimental and Numerical Study

Abstract: Intumescent coating is able to provide effective fire protection with both practicality and aesthetics. In this study, expansion performance and thermal physical property experiments are firstly carried out to obtain the basic parameters at different temperatures. Then, the thermal response model of the concrete-filled steel tubular (CFST) structure under the protection of intumescent coating in a fire is established. Finally, based on the experimental data and thermal response model, the effects of initial th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…This does not differ from the practical data, well known from works [1,3,5], the authors of which, by the way, also associate the effectiveness of fire protection with the formation of a foam coke layer under the influence of the burner flame. But, in contrast to the results of research reported in [6,7,18,19], our data on the effect of the swelling coating on the process of retarding the transfer of temperature allow us to state the following:…”
Section: Discussion Of Results Of Studying the Process Of Formation O...supporting
confidence: 55%
See 1 more Smart Citation
“…This does not differ from the practical data, well known from works [1,3,5], the authors of which, by the way, also associate the effectiveness of fire protection with the formation of a foam coke layer under the influence of the burner flame. But, in contrast to the results of research reported in [6,7,18,19], our data on the effect of the swelling coating on the process of retarding the transfer of temperature allow us to state the following:…”
Section: Discussion Of Results Of Studying the Process Of Formation O...supporting
confidence: 55%
“…The swelling coating is able to provide effective protection against fire simultaneously with practicality and aesthetics [5]. In the cited study, experiments are first conducted on the expansion performance and thermophysical properties to obtain the basic parameters at different temperatures.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%